Interoceptive Processes in Anorexia Nervosa in the Time Course of Cognitive-Behavioral Therapy: A Pilot Study - Fischer, Dana; Berberich, Götz; Zaudig, Michael; Krauseneck, Till; Weiss, Sarah; Pollatos, Olga (Frontiers in Psychiatry, 2016)
Objective: Previous studies report reduced interoceptive abilities in anorexia nervosa (AN) using various methods. Recent research suggests that different levels of interoceptive processes aiming at different subdomains of interoceptive abilities must be further distinguished as these levels can be differentially affected. Two important levels refer to interoceptive accuracy (IA) derived from objective performance tasks such as the heartbeat detection task, and interoceptive sensibility (IS) as assessed by self-report. There is a lack of studies investigating both IA and IS in AN, and examining them in the time course of therapy. Aim of the pilot study was to evaluate the different interoceptive processes – especially IA and IS – in the time course of therapy. Methods: Fifteen patients with AN (restricting type) from the Psychosomatic Clinic in Windach were investigated three times (T1, T2, T3) during a standardized cognitive-behavioral therapy and compared to fifteen matched healthy controls assessed at Ulm University in a comparable design. All participants performed the heartbeat detection task examining IA and completed standard psychological assessments including an assessment of IS. Results: Patients with AN showed a significantly decreased weight, higher levels of depression and both reduced IA and IS compared to healthy controls at T1. Following therapy, patients recovered in terms of weight and depression symptomatology. A descriptive trend for recovering from IA and IS was observed. Discussion: Our findings suggest that interoceptive deficits are present in recovered patients. Therefore, further investigations are needed with more patients, differentiating between relapsed and recovered patients, and more specific training methods to improve interoceptive processes.